Genome-wide identification of the AOMT gene family in wax apple and functional characterization of SsAOMTs to anthocyanin methylation - Wei, Xiuqing; Li, Liang; Xu, Ling; Zeng, Lihui; Xu, Jiahui (Frontiers in Plant Science, 2023)
Anthocyanins are major pigments in the peels of red-series wax apple fruits, and two principal components of them, the cyanin and the peonidin, are non-methoxylated and methoxylated anthocyanins, respectively. Anthocyanin O-methyltransferases (AOMTs) are an important group of enzymes that have the ability to catalyze anthocyanins methylation to promote the solubility, stability and bioactivity of anthocyanins. Although AOMT genes have been studied in a variety of plants, the function of them in wax apple is generally not well understood. The genome-wide analysis of the AOMT genes was performed with bioinformatics technology, and the expression patterns of different plant tissues, cultivars, fruit ripening stages and exogenous ABA treatments was analyzed by transcriptome sequencing analysis and qRT-PCR verification. An initial functional evaluation was carried out in vitro using recombinant SsAOMT5 protein.Results: Only two main compositions of anthocyanin were found in peels of two wax apple cultivars, and it was worth noting that Tub Ting Jiang cultivar contained non-methoxylated anthocyanin (Cy3G) only, while Daye cultivar contained both non-methoxylated and methoxylated (Pn3G) anthocyanins. A total of 6 SsAOMT genes were identified in the whole genome of wax apple, randomly distributing on three chromosomes. A phylogenic analysis of the protein sequences divided the SsAOMT gene family into three subgroups, and all SsAOMTs had highly conserved domains of AOMT family. In total four types of stresses related and five types of hormones related cis-elements were discovered in the promoter region of the SsAOMTs. Expression pattern analysis showed that SsAOMT5 and SsAOMT6 expressed in all tissues to varying degrees, notably, the expression of SsAOMT5 was high in the flower and fruit, and significantly higher in Daye peels than those of other cultivars in the fruit ripening period. Exogenous ABA treatment significantly increased anthocyanin accumulation, but the increase of methoxylated anthocyanin content did not reach significant level comparing without ABA treatment, while the expression of SsAOMT5 upregulated under ABA treatment. We identified two homologous SsAOMT5 genes from Daye cultivar (DSsAOMT5) and Tub Ting Jiang cultivar (TSsAOMT5), the results of functional analyses to two SsAOMT5 recombinant proteins in vitro demonstrated that DSsAOMT5 showed methylation modification activity, but TSsAOMT5 did not.